Individuals’ Self-Reactions Toward COVID-19 Pandemic in Relation to the Awareness of the Disease, and Psychological Hardiness in Saudi Arabia - Alsukah, Aljawharh Ibrahim; Algadheeb, Nourah Abdulrhman; Almeqren, Monira Abdulrahman; Alharbi, Fatimah Sayer; Alanazi, Rasis Abdullah; Alshehri, Amal Abdulrahman; Alsubie, Futiem Nasha; Ahajri, Reem Khalid (Frontiers in Psychology, 2020)
The COVID-19 outbreak around the world has caused public health concerns and changes in peoples’ behaviors and psychological distress. The pandemic impacts on human behavior, emotions, and cognition, leading to diverse reactions in relation to awareness of the disease. However, there is little understanding around the psychological impacts of the pandemic and strategies to overcome this impact. This study aimed to examine individuals’ reactions towards the COVID-19 pandemic in relation to their psychological hardiness, their degree of awareness towards the pandemic, and precautionary measures taken. Individuals living in Saudi Arabia were invited to complete an online questionnaire which included demographic items, psychological responses to the pandemic, awareness of COVID-19, and measures of psychological hardiness. A total of 1272 individuals were recruited into the study, with the majority being female (85%). Results indicated that the average psychological responses to the COVID-19 pandemic in the study sample were 75.85%. This indicates that the sample generally has a high level of positive psychological responses to the COVID-19 pandemic. The awareness of COVID-19 among Saudi was 91.50%. This indicates a high level of awareness among the study sample.